Finding the Victim of Abuse: A New Frontier of Physicians' Liability? Data From a Local Italian Experience on Minor Maltreatment - Turillazzi, Emanuela; Toni, Chiara; Turco, Sara; Di Paolo, Marco (Frontiers in Pediatrics, 2020)
Violence towards minors is a widespread phenomenon and effective programs are desperately needed to prevent it. Data from the literature showed that underreporting child/adolescents abuse has become a widespread phenomenon, exposing minors to additional harm from further potentially dangerous situations. It is proved that systematic screening and standardized procedures for minors presenting at emergency departments with the suspicion of abuse might increase the detection rate, reducing the risk of underreporting. In Italy a system of mandatory reporting is in place, and it is considered to be crucial in detecting abuse and preventing further harm to children. In this paper we report our experience with a regional (Tuscany) project named “Codice Rosa” (Pink code) introduced in 2014 with the aim to treat and protect the most vulnerable bracket of the population. We present data concerning the access of minors for suspected abuse at the emergency room of the local hospital, focusing on a case of omitted diagnosis leading to further violence episodes. According to our experience, since the introduction of the “Pink Code” there have been 43 cases of reported child abuse, with an increasing trend throughout these years (from 1 reported event in 2015 to 16 reported events in 2018). Despite the limited number of our population, the increasing trend in the reported events was particularly evident for bullying cases (n= 0 in 2015; n=4 in 2018). Despite data are still limited, the procedure proved effective in preventing child abuse, though it could still be implemented. Minor abuse and maltreatment are important health issue globally which can lead to significant physical and psychological morbidity. Implementing knowledge of healthcare professionals on how to deal with child abuse and introducing educational programs on recognition, treatment and report of child abuse is mandatory not only to prevent missing diagnosis of child and minor maltreatment, but also to reduce the risk of professional liability on different bases.